Frequency of Bullying Behavior, Sources and Coping Strategies among Student Nurses in Karachi, Pakistan - Muhmooda Abdul Razzaque (Journal of University Medical & Dental College, 2023)
Background and objective: Bullying is being increasing day by day among health care professionals and specially nursing students (NS) are victimized due to their novelty in nursing profession. The objectives of this study were to find out frequencies of bullying behavior and its association with sources (perpetrators), and coping strategies among NS in Karachi, Pakistan.